2018
DOI: 10.1158/0008-5472.can-17-3140
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Immunotherapy Using PRAME-Specific T Cells in Medulloblastoma

Abstract: Medulloblastoma is the most frequent malignant childhood brain tumor with a high morbidity.Identification of new therapeutic targets would be instrumental in improving patient outcomes. We evaluated the expression of the tumor-associated antigen PRAME in biopsies from 60 medulloblastoma patients. PRAME expression was detectable in 82% of tissues independent of molecular and histopathologic subgroups. High PRAME expression also correlated with worse overall survival. We next investigated the relevance of PRAME … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 52 publications
0
49
1
Order By: Relevance
“…Ultimately, several experimental evidences (38,39) suggest that positioning of costimulatory domains within the endodomain of a CAR can influence CAR T-cell activity, and no algorithm, up to now, is able to predict which costimulatory combination is optimal for a specific CAR construct, making the search for an optimized activity strictly dependent on experimental conditions. We recently showed the advantage of using CD28.4-1BB costimulatory domain to optimize CAR T-cell therapy targeting GD2+ neuroblastoma (40). In the current study, however, we observed an in vivo superiority of the CAR.CD30 construct incorporating the CD28.OX40 (41,42).…”
Section: Evaluation Of Persistence and Establishment Of Long-term Immcontrasting
confidence: 66%
“…Ultimately, several experimental evidences (38,39) suggest that positioning of costimulatory domains within the endodomain of a CAR can influence CAR T-cell activity, and no algorithm, up to now, is able to predict which costimulatory combination is optimal for a specific CAR construct, making the search for an optimized activity strictly dependent on experimental conditions. We recently showed the advantage of using CD28.4-1BB costimulatory domain to optimize CAR T-cell therapy targeting GD2+ neuroblastoma (40). In the current study, however, we observed an in vivo superiority of the CAR.CD30 construct incorporating the CD28.OX40 (41,42).…”
Section: Evaluation Of Persistence and Establishment Of Long-term Immcontrasting
confidence: 66%
“…7 NY-ESO-1 is expressed heterogeneously in SS, with only 56% of tumors expressing the antigen in more than 50% of the tumor cells. 11 PRAME-TCR engineered T-cells could be used for the treatment of other cancers as well, including medulloblastoma, since many tumor types express PRAME 8 10 , 12 14 . PRAME-TCR engineered T-cells are currently used for the treatment of refractory or relapsed acute myeloid leukemia (AML) in a phase I TCR-gene therapy trial (ClinicalTrials.gov NCT02743611).…”
Section: Discussionmentioning
confidence: 99%
“…Many cancer testis antigens remain MHC restricted immune targets making widespread application difficult due to the vide variance of MHC alleles across populations. However, Orlando et al recently showed some success in orthotopic medulloblastoma models using CAR-T cells specific for the PRAME-derived peptide SLL (56). This peptide, which is presented in context of HLA-A * 02, is thought to be present in up to 48.4% in caucasians and 22.6% in black ethnic groups (57).…”
Section: Antigenic Targetsmentioning
confidence: 99%